The productive autonomy of public forest-dwellers in the Amazon: two case studies of community timber management - Pacheco, Jéssica; Azevedo-Ramos, Cláudia; Nakano, Eduardo (Sustainability in Debate, 2022)
Forest-dwellers in the Brazilian Amazon public forests share the management of the territory and natural resources with governmental agencies, subjecting themselves to State rules. This study aims to evaluate the perception of stakeholders about the autonomy of traditional communities to carry out community timber forest management (CFM) in two federal protected areas. A Swot analysis revealed mismatches in priorities among stakeholder groups (Communities, Government and Partners). Four autonomy parameters were evaluated by 111 stakeholders using a satisfaction questionnaire. Communities and Government had similar perceptions of the autonomy of communities to develop CFM, while Partners were pessimistic. Stakeholders showed greater satisfaction with communities’ social organization than with their business management ability. Licensing, operational tools and administrative knowledge were perceived as bottlenecks for community enterprises. Nevertheless, targeted public policies and a minimum regulatory requirement for CFM may guarantee community autonomy to maintain their way of life and make their forest enterprises viable.